Assessing a Structured Psycho educational Intervention for Academic Stress for Tenth-Grade Students in Hassan, India: A School-Based Randomized Controlled Trial - Chanadana, Shilpa (Journal of Educational Research and Policies, 2025)
Background & Objectives: Teenage years can be stressful and challenging. Adolescents feel all kinds of pressures to do well in school, to be popular with peers, to gain the approval of parents, to make the team, to be cool. In addition, many teenagers have other special problems. It may be due to parent’s marital problems, parent being out of work or the family's financial problems, parent's alcoholism and poverty. It was found out that, academic work load, inadequate resources, low motivation, poor performance in academic, continuous poor performance in academic overcrowded lecture halls and uncertainty of getting job after graduating from the university leads to stress among students. Coping style may play an important role in the way students manage stressful academic events and perform at college. As expected, greater academic stress co-varied with lower course grades; however, students who engaged in problem-focused coping were more likely to be motivated and perform better than students who engaged in emotion-focused coping. College students confront many challenges in pursuit of their educational goals. When such experiences are perceived as negative, they can have an adverse effect on students’ motivation and performance. Difficulties in handling stress can lead to mental health problems. So, there is a need to educate the high school students regarding academic stress and coping strategies. Hence the present study was undertaken to assess the “Effectiveness of Structured Teaching Program on Knowledge regarding Academic Stress and Coping Strategies Among Tenth Standard Students in Selected High School at Hassan’’ and to find the association between knowledge, attitude and selected demographic variables of the respondents. Methods: The study involved single group pre-test and post-test without a control group using pre-experimental design, with non-probability purposive sampling. Knowledge questionnaire was administered to 30 tenth standard students. Pre-test was conducted on first day then the structured teaching programme was given in a classroom. Post- test was conducted after seven days using the same questionnaire. The results were described by using descriptive and inferential statistics. Results: The collected data was analyses by descriptive and inferential statistics. The overall pre-test mean knowledge score was 43.9% followed by post-test 81.8% with mean enhancement of knowledge score of 37.9% which is statistically significant. The paired ‘t’ test was computed and it was 24.42 which is higher than the table value and is significant at 5%. Structured teaching programme was effective in increasing the knowledge on academic stress and its coping strategies. There was a significant association between knowledge scores with demographic variables like Age, sex, type of family, family monthly income and primary care giver at early childhood at 5% level. Interpretation & Conclusion: The findings of the study showed that there was a deficit in knowledge regarding academic stress and its coping strategies. The Structured Teaching Programme (STP) was effective in improving the knowledge of tenth standard students regarding academic stress and its coping strategies.